Design and Implementation of a Cost-Effective, Network-Based Clinic Management System for Small Healthcare Facilities in Iraq - Sultan, Mohammed Muayad (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2025)
Managing clinics efficiently requires a cost-effective and user-friendly system that simplifies daily operations while maintaining data security and accessibility. This paper proposes a clinic management system that does not require a dedicated server in order to minimize costs and ease the process of setup. The system is developed using SQLite, a lightweight database management system that enables easy data management on local machines and supports networked terminals. For the best performance, we divide the data into two SQLite files; the first for the basic activities of the clinic and the second for prescriptions and other attachments to enhance the processing and use of the system. The system is developed using C# and has a friendly graphical user interface for doctors and secretaries. It has role-based access control that provides secure user authentication and database is encryption to ensure that patient’s information is well protected. The system is deployed via Windows network sharing, which makes it very easy to connect multiple terminals simultaneously through LAN or Wi-Fi without the need of professional IT personnel. This system has been used in more than 50 clinics and has proven to be reliable, efficient and easy to use and is therefore suitable for small to medium size healthcare institutions. It improves the management of the patient’s records, the flow of work, and provides a cost-effective alternative to traditional clinic management solutions.